2013
DOI: 10.1038/ijo.2013.225
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of five centrally acting drugs on the pharmacological treatment of obesity

Abstract: The centrally acting drugs DEP, FEN, MZD and SIB were more effective than PCB in promoting weight loss in obese premenopausal women, with a satisfactory benefit-risk profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 37 publications
1
40
0
3
Order By: Relevance
“…Previous studies in humans revealed that at appropriate concentrations, DEP, PHEN, and BUP produce weight loss (Hendricks et al 2009) with the order DEP Ն PHEN Ͼ BUP (Cercato et al 2009;Suplicy et al 2014). In the present study, using rats, we found that DEP20 was slightly more potent than PHEN20 with regard to weight loss (Fig.…”
Section: Comparison Of the Appetite Suppressantssupporting
confidence: 64%
“…Previous studies in humans revealed that at appropriate concentrations, DEP, PHEN, and BUP produce weight loss (Hendricks et al 2009) with the order DEP Ն PHEN Ͼ BUP (Cercato et al 2009;Suplicy et al 2014). In the present study, using rats, we found that DEP20 was slightly more potent than PHEN20 with regard to weight loss (Fig.…”
Section: Comparison Of the Appetite Suppressantssupporting
confidence: 64%
“…Modern treatment regimens for obesity combine diet, exercise, behavioral psychotherapy, and in severe cases, gastrointestinal surgery to reduce craving and resist food consumption [von Deneen and Liu, 2011]. The available pharmacological treatments for obesity are relatively ineffective and expansive, and have their drawbacks [Suplicy et al, 2014]. The available pharmacological treatments for obesity are relatively ineffective and expansive, and have their drawbacks [Suplicy et al, 2014].…”
Section: Introductionmentioning
confidence: 99%
“…Several antiobesity drugs, including diethylpropion, fenproporex, mazindol, fluoxetine, and sibutramine, have been developed [14], but there is little evidence for effective and safe treatments. …”
Section: Introductionmentioning
confidence: 99%